Traction performance of different size of cage wheel for power tiller - Pradhan, Piyush; Verma, Ajay; Guru, Prabhat Kumar; Pandey, Mukesh Kumar (ORYZA-An International Journal of Rice, 2018)
The selection of cage wheel is of primary importance in tillage operations for the optimization of traction performance. Selection of proper cage wheel helps in limiting slip and fuel consumption which involves energy loss and it also minimize time required for soil tillage. The present study aim to investigate the tractive and drawbar performance of different diameter of cage wheels. Three cage wheels of diameter 68 cm, 73 cm, and 78 cm with 300 lug angles were tested in four different water levels of 5 cm, 10 cm, 15 cm and 20 cm in wet land field conditions. Results shows that cage wheel of 73 cm diameter gave better performance in terms of higher tractive efficiency with less power consumption, than other cage wheels. Reducing the diameter of cage wheel increases the draft and sinkage and blocking of soil on lug surface. The maximum tractive efficiency was found in the range of 73-78% at 789 N to 1224 N draft and drawbar power was in the range of 505 W to 565 W.